Lemierre's syndrome: Pediatric clinical case presentation - Jennifer Richardson Maturana, MD; Sara Gomez Milanés, MD; Luz Angela Moreno Gómez, MD; Liliana Henao Gomez, MD (Radiology Case Reports)
Lemierre Syndrome (LS) is a rare infectious condition characterized by septic thrombosis of the internal jugular vein and septic embolization, mainly caused by Fusobacterium necrophorum. Diagnostic Imaging plays a key role in the early diagnosis and follow-up of the syndrome. This article reviews the available literature on radiology applied in LS and analyzes a pediatric clinical case that highlights the importance of computed tomography (CT) and magnetic resonance imaging (MRI) for identifying retropharyngeal abscesses and jugular thrombosis. The case involves a 2-month-old child diagnosed with LS complicated by mediastinitis, cervical empyema, and septic thrombosis of the internal jugular vein as complication.